PENGARUH FAKTOR FUNDAMENTAL PADA NILAI PERUSAHAAN SEKTOR TELEKOMUNIKASI DI BURSA EFEK INDONESIA TAHUN 2008-2012 - Adiputra, I Nyoman Wedana (E-Jurnal Akuntansi, 2014)
Investors need accurate information to be used as a consideration in determining the option to buy shares of companies that benefit. The information can be used as material stock analysis both fundamental and technical. The financial statements as a source of data in fundamental analysis should be able to describe the company's financial position at a given time and the results of operations at any given time is reasonable. The purpose of this study was to examine and obtain empirical evidence about the influence of return on assets, return on equity, earnings per share and the debt to equity ratio on firm value. This research was conducted in the telecommunications sector companies listed in Indonesia Stock Exchange from 2008 to 2012. Eight samples are taken based company purposive sampling method. The analysis technique used is multiple linear regression. Based on the results of the analysis found that the return on assets, return on equity, and growth of the company has a positive effect on firm value. While earnings per share and the debt to equity ratio has no effect on firm value . This indicates the higher or lower debt owned a company will not affect the value of the company, because in the Indonesian capital market stock price movement and the creation of value added enterprise market due to psychological factors.   Keywords : enterprise value, return on assets, return on equity, earnings per share, growth, debt to equity ratio